Relationship between Age, Knowledge and Husband Support with Unmet Need Incidence - Umayyah Umayyah; Hasrida Hasrida (Indonesian Journal of Global Health Research, 2025)
The high total fertility rate (TFR) and unwanted births are caused by the high level of unmet demand for family planning among women of childbearing age. Age, expertise, and spousal support are three aspects that play a role in this. Objective to analyze unmet need in relation to age, education, and husband's support. Method using a cross-sectional approach, 89 respondents were selected from a group of fertile-age couples (PUS) in BPM Umayyah, Muaragembong District, Bekasi Regency in 2024, data collection by observation and interviews. Data analysis used the chi-square test. The majority of fertile couples did not have unmet needs, based on the univariate analysis findings (65.2%), 76.4% were of reproductive age, 60.7% had sufficient knowledge, and 51.7% had supportive partners. Unmet need was found to be associated with three variables in the bivariate analysis: age (p = 0.000), knowledge (p = 0.001), and husband support (p = 0.004). The incidence of Unmet Need is correlated with husband support, age, and expertise. To avoid misunderstandings about the use of contraceptives and to motivate mothers to use contraceptives to prevent pregnancies that impact their health.